The Critical Roles of Muslim Women in the Development of Modern Education: Issues and Challenges - Yussof, Mohammad Hilmy Baihaqy (Journal of Social Transformation and Regional Development, 2021)
One of the most critical aspects in the development of a society is education. From the Quranic perspective, man and women do not come to this world accidentally without any mission and purpose in their life as the Qurâ€™Än says: â€œDid you think that We had created you in play (without any purpose), any that you would not be brought back to Us?â€ (Al-Muâ€™minun, 23:115). Thus, IslÄm has put a greater emphasize and rights on education, not specifically towards men but also women. Both men and women are equally encouraged to acquire knowledge as what was being said in the Prophetic tradition, â€œSeek knowledge from the cradle to the graveâ€. However, what are the unique critical roles of Muslim women in the development of modern education? To examine this issue, it is important to know the position of Islam in relation to education and womenâ€™s education. Generally, education can be in a formal as well as non-formal setting. Thus, it is important to identify the type of curriculums that should be provided to the Muslim women in developing their roles towards the ummah. By applying purely qualitative methods, this paper will examine the critical roles of Muslim women in education as well as the issues and challenges faced by them in carrying out their roles in the development of the modern education system.